The Impact of the Antigenic Composition of Chimeric Proteins on Their Immunoprotective Activity against Chronic Toxoplasmosis in Mice - Justyna Gatkowska; Katarzyna Dzitko; Bartłomiej Tomasz Ferra; Lucyna Holec-Gąsior; Malwina Kawka; Bożena Dziadek (Vaccines, 2019)
Toxoplasmosis may pose a serious threat for individuals with weakened or undeveloped immune systems. However, to date, there is no specific immunoprophylaxis for humans. Thus, the aim of this study was to evaluate the immunogenicity of three trivalent—SAG2-GRA1-ROP1L (SGR), SAG1L-MIC1-MAG1 (SMM), and GRA1-GRA2-GRA6 (GGG)—and two tetravalent—SAG2-GRA1-ROP1-GRA2 (SGRG) and SAG1-MIC1-MAG1-GRA2 (SMMG)—chimeric T. gondii proteins, as well as their protective potential against chronic toxoplasmosis in laboratory mice. All three trivalent recombinant proteins possessed immunogenic properties, as defined by specific humoral and cellular responses in vaccinated mice characterized by the synthesis of specific IgG (IgG1/IgG2a) antibodies in vivo and the release of Th1/Th2 cytokines by stimulated splenocytes in vitro. Immunization with all three recombinant proteins provided partial protection against toxoplasmosis, although the protective capacity strongly depended on the individual antigenic composition of each preparation. The antigens providing the highest (86%) and lowest (45%) protection, SGR and SMM, respectively, were supplemented with GRA2 antigen fragment, to form the tetravalent chimeric proteins SGRG and SMMG. Further study revealed that the tetravalent preparations exhibited high immunogenic potential; however, the addition of another antigen to the recombinant protein structure had distinct effects on the protection generated, compared to that of the trivalent counterparts, depending on the antigen tested.